Evaluating the Efficacy and Pitfalls of G-Patch: A Synthetic Fabric Patch for Duroplasty - A Retrospective Single Institute Study - Ansari, Md Safroz; Yadav, Aditya; Lamichhane, Somraj; Quazi, Masood (Nepal Journal of Neuroscience, 2025)
Introduction: The use of synthetic materials for duraplasty has been a topic of considerable interest in neurosurgery. Synthetic grafts offer several advantages over autologous tissue, including reduced operative time, decreased morbidity, and consistent availability.Methods: This is a retrospective study and analyzed data from patients who underwent duraplasty with G-Patch at a single institute. All the patients under inclusion criteria, data were collected from the hospital records, digital and hardcopies. Inclusion Criteria were all patients who underwent surgery and dura were closed using Gpatch and availability of complete medical records and follow-up data.Results: A total of 48 patients were included in this study. Most of the patient were males 68.75% (33) and 31.25%(15) females. The mean (SD) age of the population was 32.48 (20.05) years. Almost 69% (33) had traumatic brain injury where 31% (15) had non traumatic indications for surgery. Three patients 6.25% had post operative complications. Two patients had post operative wound infection, and one patient had wound infection along dehiscence. None of the patients had seizure, bleeding seroma, CSF leak or any signs of foreign body reactions.Conclusion: G-Patch appears to be safe and biocompatible, efficient, and practical option for dural closure in both traumatic and non-traumatic neurosurgical cases.